PHONETIC DIFFICULTIES OF CHINESE FOR SPEAKERS OF OTHER LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This scientific article will discuss phonetic challenges in the Chinese language, namely articulation and tones. A comparative analysis is conducted between Chinese, English and Russian. The difficulties that foreign students may face when learning a language, as well as common mistakes, are discussed. Thus, the study of phonetic difficulties in the Chinese language helps to better understand the peculiarities of its development by foreign students and suggests effective strategies for overcoming them.